Sociological studies of children and youth. Vol. 8 - Kinney, David A., 1960- (JAI, 2001)
The volumes in this series illustrate how social organization and private, emotional experience are different phases of the social process. They show the steps by which emotional experience is shaped by social structural, macro-level processes and how these processes are changed by experience.